Measuring Mass Attenuation Coefficient and Elemental Composition for Egbeda Soil Series of Southwestern Nigeria (International Journal of Scientific Research and Management (IJSRM), 2021)
Information from workers on the profitability of cassava on Iwo and Egbeda soil series in Oyo state, Nigeria have shown the Iwo soil series to be more profitable given the same scale of cassava cultivation. Therefore the need arises to improve on the soil properties of Egbeda soil series which will possibly improve the production efficiency for this category of farmers. In this work, an experimental procedure using gamma attenuation technique to determine the mass attenuation coefficient at different gamma ray energies of 59.5, 661.7, 1173.2 and 1332.5 keV, and at depths of 0 – 15, 15 – 30, 30 – 45, 45 – 60, 60 – 75 and 75 – 90 cm into the Egbeda soil series profile have been studied. Likewise X-ray fluorescence, XRF, method was used to obtain the elemental composition and concentrations at these depths while the XCOM software was applied to obtain the photon mass attenuation coefficients at the different gamma ray energies for the depths. Mass attenuation coefficients, obtained experimentally and that computed theoretically using XCOM varied exponentially with photon energy. The correlation coefficient between the experimentally-obtained and XCOM-obtained μs for the energies considered ranged from 0.89 – 0.96. The variation of with soil depth show that the top soil (0 – 15cm depths) is least attenuating with gamma ray penetrability varying down the profile. Information on the mass attenuation coefficients, elemental composition, and concentrations at varying depths into the soil profile will go a long way in contributing to efforts at improving the soil condition of the Egbeda soil series.